Preparation method of polyacrylonitrile fiber fabric for hydrogen energy stack diffusion layer electrode cloth

By cutting and spinning, weaving, pre-oxidizing and carbonizing activation treatments on the polyacrylonitrile-based carbon fiber fabric, the problems of insufficient porous adsorption characteristics and surface substrate uniformity of the carbon fiber fabric layer in the gas diffusion layer of the hydrogen fuel cell are solved, and better breathability, conductive properties and mechanical strength are achieved.

CN119507082APending Publication Date: 2025-02-25山东宽原新材料科技有限公司
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202411576846.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-06
Publication Date
2025-02-25

AI Technical Summary

Technical Problem

The porous adsorption characteristics and surface substrate uniformity of the carbon fiber fabric layer in the existing hydrogen fuel cell gas diffusion layer are insufficient, resulting in insufficient breathability, conductive properties and mechanical strength.

Method used

Polyacrylonitrile (PAN)-based carbon fiber fabric is used to form an activated carbon fiber cloth with uniform distribution and controllable properties through cutting and spinning treatment, weaving, pre-oxidation treatment and carbonization activation treatment.

Benefits of technology

The porous adsorption characteristics and surface substrate uniformity of the hydrogen fuel cell gas diffusion layer are improved, breathable performance, conductive performance and mechanical strength are enhanced, and the preparation method is simple and practical.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119507082A_ABST
    Figure CN119507082A_ABST
Patent Text Reader

Abstract

The invention belongs to the field of hydrogen fuel cell gas diffusion layer preparation, and relates to a preparation method of a polyacrylonitrile fiber fabric for hydrogen energy stack diffusion layer electrode cloth, which comprises the following four steps: cutting and spinning PAN fibers, weaving PAN yarns to form a fabric, pre-oxidizing the PAN fiber fabric, and carbonizing and activating. High-strength PAN fibers are used for weaving treatment of various fabric structures, and through specific pre-oxidation, carbonization and activation treatment, the activated carbon fiber cloth which is uniform in-plane distribution and controllable in performance distribution and is used for the diffusion layer of the hydrogen energy galvanic pile is formed, so that the porous adsorption characteristic of a carbon fiber fabric layer and the uniformity of a surface base material are improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of preparation of hydrogen fuel cell gas diffusion layers, and is a PAN-based carbon fiber active fabric, in particular to the technical field of production of active carbon fibers for electrode materials. Background Art

[0002] The information disclosed in this background technology section is only intended to enhance the understanding of the overall background of the invention, and should not necessarily be regarded as an admission or any form of suggestion that the information constitutes the prior art already known to a person skilled in the art.

[0003] A fuel cell is a device that converts chemical energy directly into electrical energy. It does not need to be charged separately. As long as the fuel and oxidant are continuously replenished, it can operate continuously to generate electricity. The electrochemical reaction rate of the fuel and oxidant in the fuel cell is very low and must be accelerated by a catalyst, so an anode catalyst and a cathode catalyst are required. Taking a polymer electrolyte fuel cell as an example, the main power generation mechanism comes from the electrode membrane group, which is often called the heart of the fuel cell. Basically, the electrode membrane group has a five-layer structure, with a polymer membrane that conducts hydrogen ions in the center, an anode catalyst layer and a cathode catalyst layer on both sides, and an outermost gas diffusion layer (often divided into a fuel gas diffusion layer and an oxygen diffusion layer).

[0004] The substrate of the gas diffusion layer structure of the proton exchange membrane fuel cell is usually a carbon fiber fabric layer, which must meet the following performance requirements: (1) a uniform porous structure, giving it excellent air permeability; (2) low resistivity, giving it high electron conductivity; (3) a compact structure and a flat surface, reducing contact resistance and improving conductivity; (4) having a certain mechanical strength, which is conducive to the production of electrodes and provides stability of the electrode structure under long-term operating conditions; (5) having chemical stability and thermal stability; and low manufacturing cost. At present, improving the porous adsorption characteristics of the carbon fiber fabric layer and the uniformity of the surface substrate have become the key technical problems that researchers are trying to solve.

[0005] Patent CN114824298A discloses a method for preparing a microporous layer in a hydrogen fuel cell gas diffusion layer, including: pre-oxidation and carbonization of polyacrylonitrile fibers. Patent CN109457430A discloses a method for preparing a carbon fiber fabric for electric heating, but the activated specific surface area of ​​the electrode cloth prepared by the above method still needs to be increased. Summary of the invention

[0006] In order to solve the above problems, the present invention provides a method for preparing an electrode cloth for a hydrogen energy stack diffusion layer by carbonization activation treatment of polyacrylonitrile-based PAN fabric, the method comprising four steps: cutting and spinning of PAN fibers, weaving of PAN yarns, pre-oxidation of PAN fiber fabrics, and carbonization activation treatment. The present invention utilizes high-strength PAN fibers to weave a variety of fabric structures, and through specific pre-oxidation, carbonization, and activation treatment, forms an activated carbon fiber cloth for a hydrogen energy stack diffusion layer with uniform in-plane distribution and controllable performance distribution.

[0007] In order to achieve the above object, the present invention adopts the following technical solution:

[0008] The first aspect of the present invention provides a method for preparing polyacrylonitrile fiber fabric for hydrogen energy stack diffusion layer electrode cloth, comprising:

[0009] The PAN fibers are cut into short strands, a sizing agent is applied on the surface of the short strands, and the short strands are twisted and combined to obtain a combined PAN fiber yarn;

[0010] weaving the combined PAN fiber yarn into a PAN fiber fabric;

[0011] The PAN fiber fabric is subjected to pre-oxidation, carbonization and activation treatment to obtain the PAN fiber fabric.

[0012] In some embodiments, the length of the chopped strands is 10-100 mm;

[0013] In some embodiments, the wetting agent is selected from at least one of a waterborne epoxy resin and a waterborne polyurethane;

[0014] In some embodiments, the coating thickness is 2-10% of the fiber diameter.

[0015] In some embodiments, the twisting is performed by two-stage group twisting, the first-stage twisting scheme is: twisting every 1-5 strands, and the twisting twist is controlled at 50-150 twists / meter; the second-stage twisting scheme is: twisting every 3-6 strands, and the twisting twist is controlled at 60-200 twists / meter;

[0016] In some embodiments, after the two-stage group twisting treatment, the two groups of PAN fibers are combined to obtain a combined PAN fiber yarn, wherein the fiber bundle ratio of the combined PAN fibers after the two-stage twisting treatment can be flexibly adjusted according to requirements, and the PAN yarn count is 10-100.

[0017] In some embodiments, the fabric structure is formed by knitting, weaving or braiding, wherein the PAN fiber fabric has a grammage of 50-500 g / m 2 .

[0018] In some embodiments, the PAN fiber fabric structure adopts a single-layer fabric structure or a multi-layer laminated structure;

[0019] In some embodiments, the number of stacked layers of the multi-layer stacked structure is flexibly adjusted according to design requirements, and the stacked thickness direction is subjected to oblique angle needle punching, wherein the needle punching angle is 20-45°, the needle punching depth is 1-3 mm, and the needle punching density is 5-10 needles / cm 2 .

[0020] In some embodiments, the pre-oxidation treatment comprises: two steps of pre-treatment under an inert atmosphere and oxidation treatment under an oxidizing atmosphere;

[0021] In some embodiments, the PAN fiber fabric is first fixed on a metal conveyor belt substrate with certain needles, wherein the substrate needle length is 0.5-2 mm and the substrate needle density is 1-2 needles / cm 2 ;

[0022] In some embodiments, the pretreatment includes: gradient heating and blast rapid cooling process, wherein the gradient heating adopts infrared heating, the final pretreatment temperature is 200-220°C, 2-4 gradients are set from room temperature to the final pretreatment temperature, and the total heating and maintenance time in each temperature gradient is controlled at 15-20min;

[0023] In some embodiments, the entire process is carried out under the protection of an inert atmosphere, using any one of nitrogen, argon, and helium;

[0024] In some embodiments, the rapid cooling by blasting uses an inert gas protection in a gradient heating process, and the blasting wind speed is controlled at 1-5 m / s, preferably 2-3 m / s.

[0025] In some embodiments, the oxidation treatment is carried out in air, and three gradient temperature zones are set at 200-230°C, 220-250°C, and 240-300°C, and the pre-oxidation time in the three temperature zones is 15-30 minutes;

[0026] In some embodiments, the oxygen index of the pre-oxidation treated PAN fiber fabric is 30-50.

[0027] In some embodiments, the carbonization treatment and activation treatment are carried out simultaneously. The pre-oxidized PAN fiber fabric is fed into the furnace of the activation furnace at room temperature, and then an inert gas is introduced into the furnace. The carbonization temperature is increased at different heating rates. After reaching a certain temperature, water vapor is introduced. After reaching a predetermined temperature, constant temperature activation is performed for a certain period of time. Finally, the carbon felt is cooled to a certain temperature under nitrogen protection, and then naturally cooled to room temperature to complete the activation and carbonization treatment of the carbon felt.

[0028] In some embodiments, the inert gas may be high-purity nitrogen, helium or argon, with a purity of more than 99.99999% and an input pressure of not less than 0.2 MPa;

[0029] In some embodiments, the heating carbonization temperature rise rate is 5-15°C / min, and the final carbonization temperature is 600-1600°C;

[0030] In some embodiments, the rate of introducing water vapor at the carbonization temperature is 3-15 g / min, the final activation time is 20-50 min, and after the activation treatment is completed, the cooling temperature under the protection of inert gas is 150-200° C.;

[0031] In some embodiments, the activated specific surface area of ​​the carbonized fiber fabric structure is 300-2000 m 2 / g.

[0032] The second aspect of the present invention provides polyacrylonitrile fiber fabric prepared by the above method.

[0033] The third aspect of the present invention provides the use of the above-mentioned polyacrylonitrile fiber fabric in the preparation of hydrogen energy stack diffusion layer electrode cloth or fuel cell.

[0034] Beneficial Effects of the Invention

[0035] (1) The present invention utilizes high-strength PAN fibers to carry out weaving treatments of various fabric structures, and through specific pre-oxidation, carbonization and activation treatments, forms an activated carbon fiber cloth for a hydrogen energy stack diffusion layer with uniform in-plane distribution and controllable performance distribution.

[0036] (2) The preparation method of the present invention is simple, practical and easy to promote. BRIEF DESCRIPTION OF THE DRAWINGS

[0037] The accompanying drawings constituting a part of the present invention are used to provide a further understanding of the present invention, and the exemplary embodiments of the present invention and their description are used to explain the present invention, and do not constitute improper limitations on the present invention.

[0038] Figure 1 This is the process flow chart of the preparation process. DETAILED DESCRIPTION

[0039] It should be noted that the following detailed descriptions are exemplary and are intended to provide further explanation of the present invention. Unless otherwise specified, all technical and scientific terms used in the present invention have the same meanings as those commonly understood by those skilled in the art to which the present invention belongs.

[0040] As described in the background technology, in order to improve the porous adsorption characteristics of the carbon fiber fabric layer and the uniformity of the surface substrate. The present invention provides a method for preparing an electrode cloth for a hydrogen energy stack diffusion layer by carbonization activation treatment of a polyacrylonitrile-based PM fabric, the method comprising four steps of cutting and spinning of PAN fibers, weaving of PAN yarns, pre-oxidation treatment of PAN fiber fabrics, and carbonization activation treatment. High-strength PAN fibers are used to weave a variety of fabric structures, and through specific pre-oxidation, carbonization, and activation treatments, an activated carbon fiber cloth for a hydrogen energy stack diffusion layer with uniform in-plane distribution and controllable performance distribution is formed.

[0041] In some embodiments, the PAN fiber is processed by a continuous synchronous cutting and spinning process. First, the PAN fiber is processed into short shreds with a length of 10-100 mm by a cutting machine, and then the PAN fiber is coated with a surface sizing agent and twisted.

[0042] In some embodiments, before the twisting treatment, a sizing agent is coated on the surface of the short-cut PAN fibers of a specific length, and the coating thickness is in the range of 2-10% of the fiber diameter, which can be flexibly adjusted according to design requirements.

[0043] In some embodiments, the coating wetting agent may be any one of aqueous epoxy resin, aqueous polyurethane, etc. and is not limited to this series of types.

[0044] In some embodiments, the coated PAN fiber adopts a two-stage twisting combination scheme, the first-stage twisting scheme is: twisting every 1-5 strands, and the twisting twist is controlled at 50-150 twists / meter; the second-stage twisting scheme is: twisting every 3-6 strands, and the twisting twist is controlled at 60-200 twists / meter.

[0045] In some embodiments, after the PAN fibers are subjected to the above-mentioned two-stage group twisting treatment, the two groups of PAN fibers are combined to obtain a combined PAN fiber yarn, wherein the fiber bundle ratio of the combined PAN fibers subjected to the two-stage twisting treatment can be flexibly adjusted according to requirements, and the final PAN yarn count is controlled within the range of 10-100.

[0046] In some embodiments, the PAN yarn woven fabric uses the above-mentioned PAN fiber shaped yarn to form a fabric structure through knitting, weaving or braiding and other weaving techniques, wherein the final PAN yarn fabric has a gram weight controlled at 50-500 g / m 2 It can be adjusted flexibly within the range.

[0047] In some embodiments, the fabric structure of the PAN yarn can adopt a single-layer fabric structure or a multi-layer laminated structure, wherein the number of laminated layers of the multi-layer laminated structure is flexibly adjusted according to the design requirements, and the laminated thickness direction is subjected to oblique angle needle punching treatment, wherein the needle punching angle (the angle between the thickness direction and the needle punching direction) is controlled within the range of 20-45°, the needle punching depth is controlled within the range of 1-3 mm, and the needle punching density is controlled within the range of 5-10 needles / cm 2 .

[0048] In some embodiments, the PAN fiber fabric pre-oxidation treatment comprises two steps: pre-treatment under an inert atmosphere and oxidation treatment under an oxidizing atmosphere.

[0049] In some embodiments, the PAN fiber fabric is first fixed on a metal conveyor belt substrate with certain needles, wherein the needle length of the substrate is controlled within the range of 0.5-2 mm, and the needle density of the substrate is controlled within the range of 1-2 needles / cm 2 The substrate can ensure the conveying and fixing of the fabric to avoid slippage and in-plane wrinkles caused by product shrinkage during the pre-oxidation process.

[0050] In some embodiments, the pretreatment process of the PAN fiber fabric pre-oxidation adopts a gradient heating and blast rapid cooling process, wherein the gradient heating adopts infrared heating, the final pretreatment temperature is in the range of 200-220°C, 2-4 gradients are set from room temperature to the final pretreatment temperature, and the total heating and maintenance time in each temperature gradient is controlled to be 15-20 minutes. The whole process is carried out under the protection of an inert atmosphere, and any one of nitrogen, argon, and helium can be used.

[0051] In some embodiments, the blast rapid cooling in the PAN fiber fabric pretreatment process adopts inert gas protection in the gradient heating process, and the blast wind speed is controlled within the range of 1-5 m / s, usually within the range of 2-3 m / s.

[0052] In some embodiments, the gradient heating and rapid cooling process of the PAN fiber fabric pre-oxidation pretreatment is mainly intended to crack the impregnation agent in the PAN fiber yarn and remove it by air blowing to avoid the generation of impurities in the PAN yarn during the subsequent pre-oxidation process.

[0053] In some embodiments, the oxidation treatment of the PAN fiber fabric under an oxidizing atmosphere is carried out in air, and three gradient temperature zones of 200-230°C, 220-250°C and 240-300°C are set. The pre-oxidation time of the three temperature zones is controlled within the range of 15-30 minutes, wherein the specific pre-oxidation temperature and treatment time of the three temperature zones can be flexibly adjusted according to design requirements, and finally the oxygen index of the PAN fiber fabric after pre-oxidation treatment is controlled within the range of 30-50, which can be flexibly adjusted.

[0054] In some embodiments, the carbonization activation treatment of the PAN-based pre-oxidized fiber fabric is carried out simultaneously with the carbonization treatment. The pre-oxidized PAN fiber fabric prepared as above is sent into the furnace of an activation furnace at room temperature, and then an inert gas is introduced into the furnace. Carbonization heating is carried out at different heating rates. After reaching a certain temperature, water vapor is introduced. After reaching a predetermined temperature, constant temperature activation is performed for a certain period of time. Finally, it is cooled to a certain temperature under nitrogen protection, and then naturally cooled to room temperature to complete the carbon felt activation and carbonization treatment.

[0055] In some embodiments, the inert gas may be high-purity nitrogen, helium or argon, with a purity of more than 99.99999%, and an input pressure of not less than 0.2MPa; the heating carbonization temperature rise rate is controlled within the range of 5-15°C / min, the final carbonization temperature is controlled within the range of 600-1600°C, the rate of water vapor introduced at the carbonization temperature is controlled within the range of 3-15g / min, the final activation time is controlled within the range of 20-50min, and after the activation treatment is completed, the cooling temperature under the protection of the inert gas is controlled within the range of 150-200°C. The activated specific surface area of ​​the carbonized fiber fabric structure finally obtained is controlled within the range of 300-2000m 2 / g range.

[0056] The present invention will be further described in detail below in conjunction with specific embodiments. It should be noted that the specific embodiments are intended to explain the present invention rather than to limit it.

[0057] Example 1

[0058] A preparation process of a PAN-based fiber fabric is specifically implemented as follows: first, the PAN fiber is processed into short shreds with a length of 10 mm by a cutting machine, and a water-based epoxy resin sizing agent with a thickness of 0.1 μm is coated on the surface of the PAN fiber. Then, the fiber is divided into two groups, one of which is twisted with 2 strands per strand and the twist is 50 twists / m; the other is twisted with 3 strands per strand and the twist is 60 twists / m. Then, the two groups of PAN fibers are combined to obtain a combined PAN fiber yarn with a count of 10.

[0059] In the second step, the above-mentioned shaped yarn is knitted to prepare a 50g / m 2Yarn fabric, the fabric adopts a single-layer fabric structure.

[0060] The third step is to fix the PAN fiber fabric on a tape with a length of 0.5 mm and a needle density of 2 needles / cm. 2 The PAN fiber fabric is fixed on a metal conveyor belt substrate to ensure that the fabric is transported and fixed to avoid slippage and in-plane wrinkles caused by product shrinkage during the pre-oxidation process. After the PAN fiber fabric is fixed, it is pretreated in a pretreatment equipment under the protection of nitrogen at a wind speed of 2m / s. The final pretreatment temperature is 200℃, and four temperature gradients are set: 50℃, 70℃, 120℃, and 200℃. The total heating and maintenance time in each temperature gradient is 15min. The pretreated fabric is then oxidized in the air. The treatment process sets three gradient temperature zones of 200℃, 250℃ and 300℃. The treatment time in each temperature zone is 15min, and finally a pre-oxidized PAN fiber fabric with an oxygen index of 30 is prepared.

[0061] The fourth step is to simultaneously perform carbonization and activation on the PAN-based pre-oxidized fiber fabric. The pre-oxidized PAN fiber fabric prepared above is fed into the furnace of an activation furnace at room temperature. The fiber is placed in the activation furnace, and high-purity nitrogen with a purity of more than 99.99999% and a pressure of not less than 0.2 MPa is introduced to simultaneously perform carbonization and activation treatment. First, carbonization treatment is performed at 600°C at a heating rate of 5°C / min. Then, when the carbonization temperature is reached, water vapor is introduced at a rate of 3g / min. After 35 minutes of activation treatment, the temperature is reduced to 150°C under the protection of an inert gas, and then naturally cooled to room temperature, and finally an activated specific surface area of ​​300m 2 / g of electrode cloth.

[0062] Example 2

[0063] The preparation process of a PAN-based fiber fabric is specifically implemented as follows: first, the PAN fiber is processed into short shreds with a length of 50 mm by a cutting machine, and the surface of the PAN fiber is coated with a water-based polyurethane sizing agent with a thickness of 0.7 μm. Then, the fiber is divided into two groups, one of which is twisted with 4 strands per group, with a twist of 80 twists / m; and the other is twisted with 5 strands per group, with a twist of 120 twists / m. Then, the two groups of PAN fibers are combined to obtain a combined PAN fiber yarn with a count of 60.

[0064] In the second step, the shaped yarn is woven into a 200 g / m 2 The yarn fabric adopts a 4-layer laminated structure, and the laminated thickness direction is needled at an oblique angle of 35° (the angle between the thickness direction and the needle direction), the needle depth is within 2mm, and the needle density is 5 needles / cm 2 .

[0065] The third step is to fix the PAN fiber fabric on a tape with a length of 1 mm and a needle density of 2 needles / cm. 2 The PAN fiber fabric is fixed on a metal conveyor belt substrate to ensure that the fabric is transported and fixed to avoid slippage and in-plane wrinkles caused by product shrinkage during the pre-oxidation process. After the PAN fiber fabric is fixed, it is pretreated in a pretreatment equipment under the protection of helium at a wind speed of 1.5m / s. The final pretreatment temperature is 220℃, and three temperature gradients are set: 80℃, 130℃, and 220℃. The total heating and maintenance time in each temperature gradient is 18min. The pretreated fabric is then oxidized in the air. The treatment process sets three gradient temperature zones of 220℃, 245℃, and 290℃. The treatment time in each temperature zone is 16min, and finally a pre-oxidized PAN fiber fabric with an oxygen index of 40 is prepared.

[0066] The fourth step is to simultaneously perform carbonization and activation on the PAN-based pre-oxidized fiber fabric. The pre-oxidized PAN fiber fabric prepared above is fed into the furnace of an activation furnace at room temperature. The fiber is placed in the activation furnace, and high-purity nitrogen with a purity of more than 99.99999% and a pressure of not less than 0.2 MPa is introduced to simultaneously perform carbonization and activation treatment. First, carbonization treatment is performed at 1200°C at a heating rate of 12°C / min. Then, when the carbonization temperature is reached, water vapor is introduced at a rate of 11g / min. After 30 minutes of activation treatment, the temperature is reduced to 180°C under the protection of an inert gas, and then naturally cooled to room temperature, and finally an activated specific surface area of ​​1500m 2 / g of electrode cloth.

[0067] Example 3

[0068] The preparation process of a PAN-based fiber fabric is specifically implemented as follows: first, the PAN fiber is processed into short shreds with a length of 90 mm by a cutting machine, and the surface of the PAN fiber is coated with a water-based epoxy resin sizing agent with a thickness of 0.65 μm. Then, the fiber is divided into two groups, one of which is twisted with 4 strands per group, with a twist of 110 twists / m; and the other is twisted with 5 strands per group, with a twist of 120 twists / m. Then, the two groups of PAN fibers are combined to obtain a combined PAN fiber yarn with a count of 90.

[0069] In the second step, the above-mentioned shaped yarn is prepared by plain weaving with a weight of 400g / m 2 Yarn fabric, the fabric adopts a single-layer fabric structure.

[0070] The third step is to fix the PAN fiber fabric on a tape with a length of 1.5 mm and a needle density of 1 needle / cm. 2The PAN fiber fabric is fixed on a metal conveyor belt substrate to ensure that the fabric is transported and fixed to avoid slippage and in-plane wrinkles caused by product shrinkage during the pre-oxidation process. After the PAN fiber fabric is fixed, it is pretreated in a pretreatment equipment under the protection of argon gas at a wind speed of 2.6m / s. The final pretreatment temperature is 215℃, and four temperature gradients are set: 40℃, 70℃, 110℃, and 215℃. The total heating and maintenance time in each temperature gradient is 16min. The pretreated fabric is then oxidized in the air. The treatment process sets three gradient temperature zones of 225℃, 245℃ and 300℃. The treatment time in each temperature zone is 28min, and finally a pre-oxidized PAN fiber fabric with an oxygen index of 45 is prepared.

[0071] The fourth step is to carbonize and activate the PAN-based pre-oxidized fiber fabric simultaneously. The pre-oxidized PAN fiber fabric prepared above is sent into the furnace of the activation furnace at room temperature. The fiber is placed in the activation furnace, and high-purity nitrogen with a purity of more than 99.99999% and a pressure of not less than 0.2MPa is introduced to simultaneously perform carbonization and activation treatment. First, carbonization treatment is performed at 1400°C at a heating rate of 12°C / min. Then, when the carbonization temperature is reached, water vapor is introduced at a rate of 13.5g / min. After 40 minutes of activation treatment, the temperature is reduced to 185°C under the protection of inert gas, and then naturally cooled to room temperature, and finally an activated specific surface area of ​​2000m 2 / g of electrode cloth.

[0072] Example 4

[0073] The preparation process of a PAN-based fiber fabric is specifically implemented as follows: first, the PAN fiber is processed into short shreds with a length of 95 mm by a cutting machine, and the surface of the PAN fiber is coated with a water-based epoxy resin sizing agent with a thickness of 0.45 μm. Then, the fiber is divided into two groups, one of which is twisted with 3 strands per group, with a twist of 110 twists / m; and the other is twisted with 5 strands per group, with a twist of 130 twists / m. Then, the two groups of PAN fibers are combined to obtain a combined PAN fiber yarn with a count of 50.

[0074] In the second step, the above-mentioned shaped yarn is prepared by weaving a 480g / m 2 The yarn fabric adopts an 8-layer laminated structure, and the laminated thickness direction is needled at an oblique angle of 30° (the angle between the thickness direction and the needle direction), the needle depth is within 2mm, and the needle density is 6 needles / cm 2 .

[0075] The third step is to fix the PAN fiber fabric on a tape with a length of 1.5 mm and a needle density of 2 needles / cm. 2The PAN fiber fabric is fixed on a metal conveyor belt substrate to ensure that the fabric is transported and fixed to avoid slippage and in-plane wrinkles caused by product shrinkage during the pre-oxidation process. After the PAN fiber fabric is fixed, it is pretreated in a pretreatment equipment under the protection of nitrogen at a wind speed of 2.3m / s. The final pretreatment temperature is 200℃, and four temperature gradients are set: 35℃, 85℃, 135℃, and 220℃. The total heating and maintenance time in each temperature gradient is 17min. The pretreated fabric is then oxidized in the air. The treatment process sets three gradient temperature zones of 228℃, 246℃ and 300℃. The treatment time in each temperature zone is 25min, and finally a pre-oxidized PAN fiber fabric with an oxygen index of 50 is prepared.

[0076] The fourth step is to simultaneously perform carbonization and activation on the PAN-based pre-oxidized fiber fabric. The pre-oxidized PAN fiber fabric prepared above is fed into the furnace of an activation furnace at room temperature. The above-mentioned fiber is placed in the activation furnace, and high-purity nitrogen with a purity of more than 99.99999% and a pressure of not less than 0.2MPa is introduced to simultaneously perform carbonization and activation treatment. First, carbonization treatment is performed at 1550°C at a heating rate of 10°C / min. Then, when the carbonization temperature is reached, water vapor is introduced at a rate of 14g / min. After 50 minutes of activation treatment, the temperature is reduced to 200°C under the protection of an inert gas, and then naturally cooled to room temperature, and finally an activated specific surface area of ​​1800m 2 / g of electrode cloth.

[0077] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. A method for preparing polyacrylonitrile fiber fabric for hydrogen energy stack diffusion layer electrode cloth, characterized in that: include: The PAN fibers are cut into short strands, a sizing agent is applied on the surface of the short strands, and the short strands are twisted and combined to obtain a combined PAN fiber yarn; weaving the combined PAN fiber yarn into a PAN fiber fabric; The PAN fiber fabric is subjected to pre-oxidation, carbonization and activation treatment to obtain the PAN fiber fabric.

2. The method for preparing the polyacrylonitrile fiber fabric for hydrogen energy stack diffusion layer electrode cloth according to claim 1, characterized in that: The length of the short shreds is 10-100 mm; Or, the wetting agent is selected from at least one of waterborne epoxy resin and waterborne polyurethane; Alternatively, the coating thickness is 2-10% of the fiber diameter.

3. The method for preparing polyacrylonitrile fiber fabric for hydrogen energy stack diffusion layer electrode cloth according to claim 1, characterized in that: The twisting adopts a two-stage group twisting process, the first-stage twisting scheme is: twisting every 1-5 strands, and the twisting twist is controlled at 50-150 twists / meter; the second-stage twisting scheme is: twisting every 3-6 strands, and the twisting twist is controlled at 60-200 twists / meter; Or, after two-stage group twisting treatment, two groups of PAN fibers are combined to obtain combined PAN fiber yarn, wherein the fiber bundle ratio of the combined PAN fibers after two-stage twisting treatment can be flexibly adjusted according to requirements, and the count of the PAN yarn is 10-100.

4. The method for preparing polyacrylonitrile fiber fabric for hydrogen energy stack diffusion layer electrode cloth according to claim 1, characterized in that: The fabric structure is formed by knitting, weaving or braiding, wherein the PAN fiber fabric has a gram weight of 50-500g / m 2 .

5. The method for preparing polyacrylonitrile fiber fabric for hydrogen energy stack diffusion layer electrode cloth according to claim 1, characterized in that: The PAN fiber fabric structure adopts a single-layer fabric structure or a multi-layer laminated structure; Alternatively, the number of laminated layers of the multi-layer laminated structure is flexibly adjusted according to design requirements, and the laminated thickness direction is subjected to oblique angle needle punching treatment, wherein the needle punching angle is 20-45°, the needle punching depth is 1-3 mm, and the needle punching density is 5-10 needles / cm 2 .

6. The method for preparing polyacrylonitrile fiber fabric for hydrogen energy stack diffusion layer electrode cloth according to claim 1, characterized in that: The pre-oxidation treatment comprises two steps: pre-treatment under an inert atmosphere and oxidation treatment under an oxidizing atmosphere; Alternatively, the PAN fiber fabric is first fixed on a metal conveyor belt substrate with certain needles, wherein the substrate needle length is 0.5-2mm and the substrate needle density is 1-2 needles / cm 2 ; Or, the pretreatment includes: gradient heating and blast rapid cooling process, wherein the gradient heating adopts infrared heating, the final pretreatment temperature is 200-220°C, 2-4 gradients are set from room temperature to the final pretreatment temperature, and the total heating and maintenance time in each temperature gradient is controlled at 15-20min; Or, the whole process is carried out under the protection of an inert atmosphere, using any one of nitrogen, argon and helium; Or, the blast rapid cooling adopts the inert gas protection of the gradient heating process, and the blast wind speed is controlled at 1-5m / s, or 2-3m / s.

7. The method for preparing polyacrylonitrile fiber fabric for hydrogen energy stack diffusion layer electrode cloth according to claim 6, characterized in that: The oxidation treatment is carried out in air, and three gradient temperature zones are set at 200-230°C, 220-250°C and 240-300°C, and the pre-oxidation time in the three temperature zones is 15-30 minutes; Or, the oxygen index of the pre-oxidation treated PAN fiber fabric is 30-50.

8. The method for preparing polyacrylonitrile fiber fabric for hydrogen energy stack diffusion layer electrode cloth according to claim 1, characterized in that: The carbonization treatment and activation treatment are carried out simultaneously. The pre-oxidized PAN fiber fabric is sent into the furnace of the activation furnace at room temperature, and then the inert gas is introduced into the furnace. The carbonization temperature is increased at different heating rates. After reaching a certain temperature, water vapor is introduced. After reaching the predetermined temperature, constant temperature activation is performed for a certain time. Finally, it is cooled to a certain temperature under nitrogen protection, and then naturally cooled to room temperature to complete the activation and carbonization treatment of the carbon felt. Alternatively, the inert gas may be high-purity nitrogen, helium or argon, with a purity of more than 99.99999% and an input pressure of not less than 0.2 MPa; Or, the heating carbonization temperature rise rate is 5-15°C / min, and the final carbonization temperature is 600-1600°C; Or, the rate of introducing water vapor at the carbonization temperature is 3-15 g / min, the final activation time is 20-50 min, and after the activation treatment is completed, the cooling temperature under the protection of inert gas is 150-200°C; Or, the activated specific surface area of ​​the carbonized fiber fabric structure is 300-2000m 2 / g.

9. Polyacrylonitrile fiber fabric prepared by the method according to any one of claims 1 to 8.

10. Use of the polyacrylonitrile fiber fabric according to claim 9 in preparing diffusion layer electrode cloth for hydrogen energy stack or fuel cell.

Citation Information

Patent Citations

  • Preparation method of carbon fiber fabric for electric heating

    CN109457430A